PTH-167 The Investigation of Dyspepsia in Primary Care- The Burning Truth. (4th June 2013) - Beg, S; Hughes, M; Raza, M; Morris, D L
Abstract : Introduction: Dyspepsia is a common symptom, thought to affect up to 46% of the population 1 . In order to streamline investigation and management in primary care, guidelines have been formulated by both the BSG and NICE. These advocate that prior to endoscopy patients are reviewed with respect to precipitating medications, helicobacter pylori (HP) status and are trialled on a proton pump inhibitor (PPI) 1, 2 . Methods: Using our computer based endoscopy database we retrospectively reviewed the direct access GP referrals for the endoscopic investigation of dyspepsia and reflux. We examined 260 cases referred to the North and East Hertfordshire NHS trust between January and December 2012 looking for adherence to guidelines. Results: In our cohort 56% were female, with the average age of patients being 55.8 years old. 10% were considered to be urgent referrals, whilst 16.5% were referred via the two week wait. Only 30% patients were tested for HP status prior to investigation, with 10 patients having had serology and 80 tested using stool antigen testing. Just 15 patients (6%) in the cohort tested positive for HP by either serology, stool antigen, CLO or gastric biopsy. A greater proportion received a trial of a PPI, 53.8% receiving a full course, whilst 36.5% had used a PPI inconsistently and 9.6% had never tried a PPI. Only 45 patients (17%) had both HP testing and a trial of a PPI. An alternate cause of pathology was considered in 12 patients with investigation with an abdominal ultrasound, in 3 cases this was as a consequence of the endoscopist's suggestion. The most common findings on endoscopy were oesophagitis, gastritis and duodenitis, 21% of examinations were entirely normal. Four cancers were identified within the 46 two week wait referrals. Conclusion: Our data has confirmed that the patients in this cohort received inadequate work up in primary care, leading to unnecessary endoscopic investigation. The average age of the patients in this group indicates that many were at an age where pathology such as malignancy would be highly unlikely. Lack of adherence to guidelines is likely to be the reason for the low diagnostic yield of significant pathology, although our endoscopic findings are consistent with those of previous studies1. The low prevalence of helicobacter may represent a reduction in its prevalence, although it is difficult to know whether this is a consequence of inappropriate testing whilst on PPI therapy, the socioeconomics of our cohort or due to HP patient positive patients treated in primary care rather than referred for endoscopy. Improved use of guidelines and dialogue between primary and secondary care should improve patient selection for the endoscopic investigation of dyspepsia. Disclosure of Interest: None Declared. References: Dyspepsia: management of dyspepsia in adults in primary care, 2004 BSG: Dyspepsia management guidelines, 2002